2011
DOI: 10.1007/s10162-011-0260-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation of Olivocochlear Fibers in Cochlear Potentials in the Chinchilla

Abstract: The mammalian cochlea has two types of sensory cells; inner hair cells, which receive auditory-nerve afferent innervation, and outer hair cells, innervated by efferent axons of the medial olivocochlear (MOC) system. The role of the MOC system in hearing is still controversial. Recently, by recording cochlear potentials in behaving chinchillas, we suggested that one of the possible functions of the efferent system is to reduce cochlear sensitivity during attention to other sensory modalities (Delano et al. in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…As mentioned in Results, we consistently found that contralateral sounds produced substantial CAP-amplitude reductions and no measurable effects on CMs in anesthetized chinchillas and small CM enhancements in only three of the seven awake chinchillas. This absence or weakness of efferent effects on CMs in the present results is consistent with results obtained in a previous study in which we electrically stimulated MOC fibers in chinchilla and obtained significant CAP reductions of up to 11 dB (for 2 kHz tones) accompanied by much smaller CM increases of <2.5 dB (Elgueda et al, 2011 ). The lesser efferent effects on CMs than on CAPs have also being reported for sustained contralateral noise that elicits sizable CAP suppressions and only small CM enhancements (Larsen and Liberman, 2009 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As mentioned in Results, we consistently found that contralateral sounds produced substantial CAP-amplitude reductions and no measurable effects on CMs in anesthetized chinchillas and small CM enhancements in only three of the seven awake chinchillas. This absence or weakness of efferent effects on CMs in the present results is consistent with results obtained in a previous study in which we electrically stimulated MOC fibers in chinchilla and obtained significant CAP reductions of up to 11 dB (for 2 kHz tones) accompanied by much smaller CM increases of <2.5 dB (Elgueda et al, 2011 ). The lesser efferent effects on CMs than on CAPs have also being reported for sustained contralateral noise that elicits sizable CAP suppressions and only small CM enhancements (Larsen and Liberman, 2009 ).…”
Section: Discussionsupporting
confidence: 94%
“…It has been shown that stimulation of the MOC efferent system by means of electrical pulses delivered at the floor of the fourth ventricle produces a decrease in the amplitude of auditory-nerve compound action potentials (CAP) and a concomitant increase in cochlear microphonic (CM) potentials (Galambos, 1956 ; Fex, 1959 ; Desmedt and Monaco, 1961 ; Gifford and Guinan, 1987 ; Elgueda et al, 2011 ). Auditory efferent fibers can also be activated by acoustic stimulation of the contralateral ear producing a decrease in single auditory-nerve fiber and CAP responses to ipsilateral tones (Buño, 1978 ; Liberman, 1989 ; Warren and Liberman, 1989a ).…”
Section: Introductionmentioning
confidence: 99%
“…The olivocochlear system has two anatomically and functionally different sub-systems: the lateral and medial olivocochlear fibers [8], [36]. Electrical activation of MOC fibers decreases CAP amplitudes and increases CM potentials [14], [15], while LOC activity can reduce or increase CAP amplitudes, without affecting CM potentials [16][18]. Electrophysiological studies at the level of the inferior colliculus suggest the presence of two functionally different colliculo-cochlear pathways which modulate the activity of medial and lateral olivocochlear fibers, thus regulating that of outer hair cells, and of auditory nerve afferent fibers respectively [19], [20], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MOC neurons, the OC system is also constituted by lateral olivocochlear neurons (LOC) which make synapses with auditory nerve fibers. Consequently, a modulation of LOC activity would only affect CAP but not CM responses (Groff and Liberman 2003), while a MOC modulation can change CAP and CM amplitudes (Elgueda et al 2011).…”
Section: Corticofugal Effects On Cap and CM Responsesmentioning
confidence: 99%